PRODUCTION OF ENGLISH CONSONANT CLUSTERS BY INDONESIAN EFL LEARNERS - Istiqomah Istiqomah; Suprayogi Suprayogi (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This study investigates how English Foreign Language (EFL) learners in Indonesia pronounce English Consonant Clusters. Several points must be mastered by the learners when they learn English such as writing, listening, reading and speaking. From those points, speaking is one of the essential points since language is used to communicate by speaking. In learning English as a second language, there are several mispronunciations made by the learners when they speak especially when they face consonant clusters since they have different phonological systems and they do not know how to pronounce them correctly. It makes them have mispronunciations and it can lead the misperception, misunderstanding and miscommunication among the speakers and the listeners. The result revealed that there were eight types of incorrect consonant clusters that the writer asked to the participants such as [ʃr], [θr], [sk], [br], [spl], [skr,] [skw], and [ksp]. Among those types of consonant clusters, there were three types of consonant clusters pronounced incorrectly by the participants such as [ʃr], [θr], and [sk]. Then, the five types of consonant clusters such as [br], [spl], [skr,] [skw], and [ksp]. However, several of them tried to challenge themselves to pronounce English words correctly even though they faced some difficulties in every word by forcing their pronunciation so that they could switch the word to an easier version of phonemes. Although they changed those words to the easier version, it would impact how the misunderstanding occurred since the sound produced was different. Keywords: English consonant clusters, EFL, phonetic, phonology